Pengembangan Komik Biologi Pada Materi Pteridophyta Untuk Siswa SMA: (Development of Biological Comics on Pteridophyta Material for High School Students) - Karlena Karlena; Revis Asra; Bambang Hariyadi (BIODIK, 2021)
This research is the background of the problems that occur in school, namely, lack of interest in reading in students, students tend to choose subjects they like and student learning outcomes are still low seen from their KKM scores. The research objective was to develop comics on Pteridophyta material for class X SMA Negeri 2 Sungai Penuh. The research method uses development research with the ADDIE model. The stages include Analysis, Disgn, Development, Implementation and Evaluation. Products in the form of comics are needed to attract students' interest in reading. Products are validated by media experts and material experts. Validation by material experts was carried out 3 (three) times, with a final percentage of 80% meaning that the comic was in the valid category with a reasonable conclusion to be produced with revisions according to the suggestions. Meanwhile, the validation by media experts was carried out 2 (two) times by obtaining a percentage of 88%, meaning that the comic was in the very valid category with the conclusion that it was feasible to be produced with revisions according to the suggestions. The comic on Pteridophyta material for high school class X students obtained practical feasibility in the very good category. Practical feasibility was obtained from teachers and students in group trials. Eligibility of the teacher with a percentage of 88.24%, small group trials with a percentage of 85.33%, trials of two large groups with a percentage of 84.67% and 84.08% respectively. From the two large group trials, an agreement was obtained that strong and significant enough regarding the feasibility of comics on Pteridophyta material for class X high school students. Thus, the development carried out on products in the form of comics on Pteridophyta material can be produced and used in Biology learning in class X. Abstrak. Penelitian ini melatar belakangi masalah yang terjadi disekolah diantaranya yaitu, Kurangnya minat baca pada siswa, siswa cenderung memilih mata pelajaran yang disukai dan hasil belajaar siswa yang masih rendah dilihat dari nilai KKM-nya. Tujuan penelitian adalah untuk mengembangkan komik pada materi Pteridophyta untuk siswa kelas X SMA Negeri 2 Sungai Penuh. Metode penelitian menggunakan penelitian pengembangan dengan model ADDIE. Tahapan meliputi Analys, Disgn, Development, Implementation dan Evaluation. Produk berupa komik dibutuhkan untuk menarik minat baca siswa. Produk di validasi oleh ahli media dan ahli materi. Validasi  oleh  ahli  materi dilakukan  sebanyak  3  (tiga) kali,  dengan memperoleh  persentase akhir  80% artinya  komik  berada  dalam kategori valid dengan kesimpulan layak  untuk  diproduksi  dengan  revisi sesuai  saran. Sedangkan  validasi  oleh  ahli  media dilakukan  2  (dua)  kali dengan memperoleh  persentase 88%,  artinya  komik  berada dalam kategori sangat valid dengan kesimpulan layak untuk diproduksi dengan revisi sesuai saran. Komik pada  materi Pteridophyta  untuk  siswa  SMA  kelas X memperoleh kelayakan  secara  praktis dengan  kategori  sangat  baik. Kelayakan  praktis  diperoleh dari guru  dan siswa  pada  uji coba  kelompok. Kelayakan  dari guru dengan  persentase sebesar  88,24%, ujicoba  kelompok kecil dengan persentase 85,33%, uji coba dua kelompok besar dengan masing-masing  persentase 84,67%  dan  84,08%.Dari  uji coba  dua  kelompok  besar didapat kesepakatan  yang  cukup  kuat dan  signifikan  mengenai  kelayakan komik pada materi Pteridophyta untuk siswa SMA kelas X. Dengan demikian, pengembangan yang dilakukan pada produk berupa komik pada materi Pteridophyta dapat diproduksi dan digunakan dalam pembelajaran Biologi pada kelas  X.